1984
DOI: 10.1056/nejm198407053110103
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic Secretion of Corticotropin-Releasing Factor as a Cause of Cushing’s Syndrome

Abstract: Corticotropin-releasing factor, a hypophyseo-tropic hormone that stimulates adrenocorticotropic hormone (ACTH) secretion, has recently been isolated, characterized, and synthesized in the sheep and rat. We report on a patient with metastatic carcinoma of the prostate presenting with anterior and posterior pituitary hormone deficiency together with ACTH-dependent Cushing's syndrome. At postmortem examination, large areas of the median eminence and pituitary stalk were replaced by tumor, but the corticotrophs we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0
3

Year Published

1986
1986
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 270 publications
(65 citation statements)
references
References 24 publications
0
62
0
3
Order By: Relevance
“…Tumor markers ACE, CA 15-3, CA 19-9, NSE and a-fetoprotein were all in the normal range except b-LPH at 366 pg/ml (normal range 85G39). Tomography emission positron imaging showed increased uptake of 18 F-fluoride in the liver, while no uptake of 111In-pentetreotide was observed on liver scintigraphy. The patient rapidly underwent left hepatectomy with apparent complete removal of the tumor.…”
Section: Patientmentioning
confidence: 89%
See 2 more Smart Citations
“…Tumor markers ACE, CA 15-3, CA 19-9, NSE and a-fetoprotein were all in the normal range except b-LPH at 366 pg/ml (normal range 85G39). Tomography emission positron imaging showed increased uptake of 18 F-fluoride in the liver, while no uptake of 111In-pentetreotide was observed on liver scintigraphy. The patient rapidly underwent left hepatectomy with apparent complete removal of the tumor.…”
Section: Patientmentioning
confidence: 89%
“…This hypothesis of the tumoral source of circulating plasma ACTH is reinforced by the finding that 2 months after tumor resection, the pituitary ACTH secretion was low, suggesting the suppression of pituitary ACTH secretion during the active phase of the disease rather than its stimulation by circulating CRH. The low level of ACTH immunoreactivity in the tumor tissue may thus be explained by reduced ACTH storage (18).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Animal and clinical studies have demonstrated that HPA axis activation by corticotropinreleasing hormone (CRH) or by stress leads to an increase in the number and size of corticotropes in the pituitary gland (Asa et al, 1992;Carey et al, 1984;Gertz et al, 1987;Westlund et al, 1985). This increase in the size and numbers of corticotropes can increase pituitary volume in humans as Figure 3 Individual measures of pituitary volumes in first-episode patients (n ¼ 77; one subject on which we had no medication history was excluded from this analysis) divided by antipsychotic treatment (free, n ¼ 18; atypicals, n ¼ 26; typicals, n ¼ 33).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the GRF receptor in dwarf mouse strains, snell (dw), and little (lit) indicated that in addition to regulating growth hormone secretion, GRF plays a crucial role in the ontogeny and proliferation of somatotropes (24,37). CRF has also been implicated in regulating cell growth, both in corti- Biochemistry: Kishimoto et aL cotrope hyperplasia (38) and in human small cell lung cancer cells, where CRF stimulates clonal cell growth that is reversed by ahel CRF-(9-41) (39). It is tempting to speculate that CRF or a mammalian sauvagine homolog is involved in the autocrine or paracrine regulation of myocyte growth and hypertrophy.…”
Section: E-qe--neekkskv--h--v-i-mentioning
confidence: 99%